Career Development of Early Childhood Teachers: Analysis of Emotional Maturity, Career Planning, and Professional Competence - Farida Mayar; Felyn Ayanda (Lembaga Yasin AlSys, 2026)
This study aims to analyze the relationship among emotional maturity, career planning, and professional competence in supporting the career development of early childhood education (PAUD) teachers. A qualitative descriptive-analytical approach was employed through a literature study, with relevant sources identified from Google Scholar, Scopus, Web of Science, and Sinta. The findings indicate that PAUD teacher career development is a continuous process shaped by the integration of three key factors. Emotional maturity contributes to teachers’ psychological resilience and self-efficacy, career planning supports the systematic determination of professional development goals and strategies, and professional competence serves as a central indicator of teacher performance quality. These three dimensions are interrelated and form a holistic framework for sustainable teacher career development. The study concludes that an integrative approach combining emotional maturity, career planning, and professional competence is essential for designing more comprehensive and sustainable PAUD teacher development programs. These findings contribute to the literature on teacher professional development by emphasizing the need for multidimensional career development frameworks that can strengthen teacher quality and improve early childhood education in Indonesia.